Cytoskeleton as a generator of characteristic physical properties of plant cells: ‘cell wall,’ ‘large vacuole,’ and ‘cytoplasmic streaming’ - Amari Toshiki; Noriko Nagata; Motoki Tominaga; Hirotomo Takatsuka (Biophysics and Physicobiology)
As sessile organisms, plants must constantly adapt to ever-changing environmental conditions. To survive in their habitats, plants have evolved characteristic cellular features that make the cells rigid yet dynamic. These include the cell wall, large vacuole, and cytoplasmic streaming. The cell wall is an elaborate extracellular matrix that surrounds plant cells and provides both physical strength and protection against external forces. The large vacuole is a membrane-bound organelle absent in animal cells. They can absorb water and expand, thereby exerting a force on the cell wall from within and generating turgor pressure that promotes cell expansion. In the narrow cytoplasmic space between the vacuole and the cell wall, intracellular components circulate via rapid flows, a phenomenon known as cytoplasmic streaming. In this review, we summarize how these three characteristic features of plant cells are organized with the help of cytoskeletal elements. This review article is an extended version of the Japanese article, “Cell Wall,” “Large Vacuole,” & “Cytoplasmic Streaming”: How Do Cytoskeletons Build Plant Cells with Unique Physical Properties?” by Takatsuka et al., published in SEIBUTSU BUTSURI Vol. 64, p. 132–136 (2024).